The heat treatment influence on the main quality indicators of Ag/n-n+GaAs heterojunctions - Dmitriev, Vadim (Видавництво Львівської політехніки, 2017)
The effect of heat treatment on the parameters and characteristics of Ag/n-n+GaAs heterojunctions is studied. Various methods for the Schottky barrier height and the nonideality factor determining have been examined and tested. The most accurate method for determining the heterojunction parameters using the current-voltage characteristic was found.
Keywords: heterojunction; current-voltage characteristic; barrier height; nonideality factor; silver